2009
DOI: 10.1080/16506070802408086
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Web-Based Cognitive Behavioural Therapy of Mild to Moderate Depression: A Randomized Controlled Trial with a Long-Term Follow-Up

Abstract: Depression is common but undertreated. Web-based self-help provides a widely accessible treatment alternative for mild to moderate depression. However, the lack of therapist guidance may limit its efficacy. The authors assess the efficacy of therapist-guided web-based cognitive behavioural treatment (web-CBT) of mild to moderate depression. Fifty-four individuals with chronic, moderate depression participated in a randomized wait-list controlled trial, with an 18-month follow-up (immediate treatment: n = 36, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
90
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(110 citation statements)
references
References 51 publications
14
90
1
5
Order By: Relevance
“…This can be explained by the fact that higher scores leave more room for improvement, which replicates earlier findings (Ruwaard et al, 2009;Spek et al, 2008). This result is also in line with findings from a metaregression analysis (Bower et al, 2013).…”
Section: Comparison With Prior Worksupporting
confidence: 81%
See 1 more Smart Citation
“…This can be explained by the fact that higher scores leave more room for improvement, which replicates earlier findings (Ruwaard et al, 2009;Spek et al, 2008). This result is also in line with findings from a metaregression analysis (Bower et al, 2013).…”
Section: Comparison With Prior Worksupporting
confidence: 81%
“…As with traditional CBT, studies evaluating the role of initial severity of depression on outcome of Internet-based treatment show mixed results; in a trial evaluating Internetbased CBT for mild to moderate depression it was found that the number of previous episodes of depression was negatively associated with improvement at 6 months follow-up (Andersson, Bergströ m, Holländare, Ekselius, & Carlbring, 2004). Better outcomes were found for participants with higher depression severity in some studies (Ruwaard et al, 2009;Spek et al, 2007). However, in another study baseline severity of depression was not related to the effect of computerized CBT (Proudfoot et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…A few studies, including one systematic review, have evaluated therapeutic alliance in guided Internet-delivered CBT for several conditions, mainly com pared with wait-listed controls or email-based therapist interaction. [54][55][56][57][58][59] These studies consistently showed high therapeutic alliance for guided Internet-delivered CBT. Only one RCT directly compared guided with face-to-face Internetdelivered CBT.…”
Section: What Are the Disadvantages Of Internet-delivered Cbt?mentioning
confidence: 90%
“…For example, in the study by Knaevelsrud and Maercker, 86% of the participants receiving treatment for posttraumatic stress experienced their contact with their online therapist as personal and 76% were positive to being treated online instead of by faceto-face CBT (Knaevelsrud & Maercker, 2007). Ruwaard et al (2009) found similar results were 87% experienced online therapy as pleasant and 89% did not miss face-to-face contact.…”
Section: Therapeutic Alliance In Internet-based Treatmentsupporting
confidence: 65%